2015
DOI: 10.1039/c5ra10624a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced formaldehyde selectivity in catalytic methane oxidation by vanadia on Ti-doped SBA-15

Abstract: During catalytic methane oxidation V/Ti-SBA-15 showed an improved selectivity towards formaldehyde over all conversions compared to V/SBA-15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…On the other hand, if the results obtained under high space velocity but with CH 4 :O 2 ratios of 2 and 9 are compared, it can be concluded that, both with and without NO addition, an increased formaldehyde space-time yield is achieved when the higher CH 4 :O 2 ratio is used, though at the expense of a decrease in conversion, which is in accordance with previous results found in the literature [31,32].…”
Section: Partial Oxidation Of Methane With the Xvsi Catalystssupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, if the results obtained under high space velocity but with CH 4 :O 2 ratios of 2 and 9 are compared, it can be concluded that, both with and without NO addition, an increased formaldehyde space-time yield is achieved when the higher CH 4 :O 2 ratio is used, though at the expense of a decrease in conversion, which is in accordance with previous results found in the literature [31,32].…”
Section: Partial Oxidation Of Methane With the Xvsi Catalystssupporting
confidence: 91%
“…catalyst is ascribed to the larger proportion of V-O-Si species on the surface, which are associated with well-dispersed tetrahedrally coordinated monomeric or slightly oligomerized VO 4 species [31][32][33][34][35][36]. The yield of formaldehyde when using this catalyst is on the order of the most active catalysts based on V-silica found in the literature, e.g., the MCM-41-supported V catalyst [31], but with the advantage of being prepared by a one-pot, single-step and less-expensive sol-gel method.…”
Section: Partial Oxidation Of Methane With the Xvsi Catalystsmentioning
confidence: 99%
“…Formaldehyde is an important intermediate in the chemical industry. 1,2 The world production of formaldehyde from methanol uses a heterogeneous catalytic process based on silver 3 or FeMo catalysts. 4 The silver-catalyzed process is being replaced by the FeMo catalyzed process because of the high formaldehyde yield and longer lifetime of the catalyst, although the lifetime is still rather short ($1 year) due to deactivation, which is a major problem.…”
Section: Introductionmentioning
confidence: 99%
“…At very low residence times the reaction can be controlled partially. During recent years, researchers focused their studies on methods to increase the productivity of this reaction [29][30][31] and found that a CH 2 O space-time yield above 5 kg CH 2 O •kg cat −1 •h −1 is possible by using an optimized mesoporous silica supported VO x catalyst [32,33]. Ohkubo and Hirose transformed methane directly to methanol and formic acid via chlorine dioxide radicals under photoirradiation [34].…”
Section: Introductionmentioning
confidence: 99%